GLOBAL TRENDS AND LOCAL FEATURES OF THE DEVELOPMENT OF MODERN CIVIL SOCIETY (International relations and international law Journal, 2025)
This study examines the complex dynamics of civil society development in the modern world, characterized by the interaction of global trends and local features. The work is devoted to a comprehensive analysis of the evolution of institutions of civic participation in the context of a changing system of international relations. The purpose of the research is to identify and scientifically analyze the systemic relationships between global trends and local trajectories of civil society development. The work is aimed at identifying key global trends in the development of civil society, conducting a comparative analysis of regional models of civic participation and studying the impact of digitalization on the transformation of forms of civic engagement. The research methodology is based on an interdisciplinary approach integrating theoretical concepts and methods of political science, sociology and international relations. Systematic, comparative, institutional and constructivist approaches are used, as well as methods of content analysis. The main results of the study demonstrate ambiguous and contradictory trends in the development of civil society, due to the dialectic of global and local. The key mechanisms of adaptation of universal models of civic participation to specific socio-cultural and political contexts, as well as the impact of global crises on the institutional development of civil society in various regional contexts, have been identified. The value of the research lies in systematizing knowledge about the transformation of traditional forms of civic engagement under the influence of digitalization and globalization, as well as in identifying new opportunities for transnational cooperation between non-state actors in a changing international environment.